The Implementation of Contextual Teaching and Learning on English Grammar Competence - Imam Nur Aziz; Yuli Ani Setyo Dewi (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
The research was aimed to the effectiveness of Contextual Teaching and Learning (CTL) in teaching grammar. Experimental study of pretest-posttest was used in this research. Non-randomize sampling was used as sampling technique. The validity test was calculated using point biserial correlation, and reliability test was 0.848 which was calculated by using K-R 21 formula. In analyzing the data, researcher used ANCOVA. The result shows that average score of pretest was 60,95 for experimental group and 60,00 for control group. The average score of posttest was 85,95 for experimental group and 78,9 for control group. The calculation of ANCOVA found that the value of F is 8.7 and F critical with df 76 at 0.01 level of significance 6.96. it means that F value was higher the F critical. From the result of data analysis showed that Contextual Teaching and Learning (CTL) gave effect on teaching grammar for 7th grade students of junior high school.